CONTENT ANALYSIS OF WHEN ENGLISH RINGS A BELL STUDENTâS TEXTBOOK - Maria Melati Sitorus; Lauren Hotmauli Silalahi; Hana Rajagukguk; Erikson Saragih (Indonesian EFL Journal, 2021)
This study's objective was for analyzing materials relevance in psychomotor and cognitive-based on 2013 English curriculum of competence in Textbook of the eighth grade of junior high school "English Rings a Bell". The methodology of this study is qualitative. Based on Anderson and Krathwol (2001) theory, The Textbook analysis consists of Simpson's and cognitive domain of taxonomy (1972) which aim to focus more on material's relevance in the textbook. The instruments for data collection used were the analysis of document and checklist observation. The study found that 23 materials consist 74.19% relevance in the cognitive domain, 7 materials consist 22.58% relevance, and 1 material only consists 3.2% relevance. While the psychomotor domain found that 10 materials consist 32.25% relevance and 11 materials consist 35.48% relevance. Therefore, the researcher concluded that in the cognitive domain, the textbook's materials are relevant to the 2013 curriculum. Although its lack of materials is relevant to the psychomotor domain. Keywords: Textbook analysis; When English Rings a Bell; 2013 curriculum; cognitive domain; psychomotor domain.